PENGUKURAN KEPUASAAN PENGGUNA WEBSITE VIU.COM DENGAN MENGGUNAKAN PENDEKATAN WEBQUAL 4.0 DAN IMPORTANCE PERFORMANCE ANALYSIS - Michkael Feb; Retno Setyorini (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2019)
Abstract, At the moment the website into one container business to sell products or services online, using website the company's target market will be more extensive. One company that follow the trend is Viu.com. Viu.com ventures streaming video service providers of entertainment Films and TV Series. This study aims to determine the level of customer satisfaction viu.com website by analyzing the gaps (gap) between the performance (perception) and interests (expectations). This research is quantitative descriptive by using WebQual 4.0 as dimensional approach usability, information quality, and service interaction. Data were analyzed using Importance-Performance Analysis. Respondents who studied amounted to 100 people by using purposive sampling technique.Research results are obtained as a whole there is a gap which is negative (-0.45). The greatest gap value is present on the dimension of the service interaction of (-0.62). From these results, it can be drawn the conclusion that the level of a quality perceived website cannot meet the level of quality expected by the user. There are also the attributes or indicators that became the focus of the improvements the company i.e. the appearance of the website, security of the personal data of the user, and the service received as promised.